2012
DOI: 10.1111/j.1744-6198.2011.00226.x
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Literature: Evaluating Dietary Intake of Filipino Americans at Risk for Type 2 Diabetes

Abstract: The purpose of this literature review is to investigate the research on the dietary intake of Filipino Americans. Evaluating the dietary practices of Filipino Americans may have an effect on the development of type 2 diabetes. Data collection was obtained, and four databases were included: Pub Medical, Cumulative Index of Nursing and Allied Health Literature, Journals at OVID, and Medline. The key words used in the search were "diet,""type 2 diabetes," and "Filipinos." A total of nine articles were relevant an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The study had indicated that Filipinos tend to develop an acculturated Westernized diet, which is associated with a higher risk for CVDs, hypertension, type 2 diabetes, and metabolic syndrome [14]. The prevalence of CVD risk factors among Filipino immigrants in the US might due to higher rates of smoking (17.7%) [12], lower levels of HDL-C (mean ± SD: 40.8 ± 0.2 mg/ dL) [47], overweight or obesity (BMI ≥ 25 kg/m 2 , 60.4%) [48], abdominal obesity (> 88 cm, 84.9%) and physical inactivity (48%) [49], high carbohydrate, sodium and fat diet [50,51], and chronic conditions such as dyslipidemia (30.2%), diabetes (8.7%) and hypertension (41.2%) which are known CVD risk factors [52]. Additionally, the prevalence of CVD risk factors among Filipino American women increased at a BMI as low as 23-24.9 kg/ m 2 to ≥ 30 kg/m 2 , including diabetes (HbA1c ≥ 6.5%, 6.38 ± 2.61 to 6.40 ± 1.08, respectively) and hypertension (SBP ≥ 140 mmHg, 125 ± 15 to 139 ± 19, respectively; or DBP ≥ 90 mmHg, 81 ± 8.4 to 87 ± 12, respectively), at a higher TG (≥ 150 mg/dL, 110 ± 55 to 142 ± 79, respectively), and at a lower HDL-C level (≤ 60 mg/dL, 60 ± 13 to 55 ± 14, respectively) [53].…”
Section: Discussionmentioning
confidence: 99%
“…The study had indicated that Filipinos tend to develop an acculturated Westernized diet, which is associated with a higher risk for CVDs, hypertension, type 2 diabetes, and metabolic syndrome [14]. The prevalence of CVD risk factors among Filipino immigrants in the US might due to higher rates of smoking (17.7%) [12], lower levels of HDL-C (mean ± SD: 40.8 ± 0.2 mg/ dL) [47], overweight or obesity (BMI ≥ 25 kg/m 2 , 60.4%) [48], abdominal obesity (> 88 cm, 84.9%) and physical inactivity (48%) [49], high carbohydrate, sodium and fat diet [50,51], and chronic conditions such as dyslipidemia (30.2%), diabetes (8.7%) and hypertension (41.2%) which are known CVD risk factors [52]. Additionally, the prevalence of CVD risk factors among Filipino American women increased at a BMI as low as 23-24.9 kg/ m 2 to ≥ 30 kg/m 2 , including diabetes (HbA1c ≥ 6.5%, 6.38 ± 2.61 to 6.40 ± 1.08, respectively) and hypertension (SBP ≥ 140 mmHg, 125 ± 15 to 139 ± 19, respectively; or DBP ≥ 90 mmHg, 81 ± 8.4 to 87 ± 12, respectively), at a higher TG (≥ 150 mg/dL, 110 ± 55 to 142 ± 79, respectively), and at a lower HDL-C level (≤ 60 mg/dL, 60 ± 13 to 55 ± 14, respectively) [53].…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy in results pertinent to individual genotype association with T2DM might obviously be due to innate genetic diversity among ethnicities in addition to multiple interactive environmental factors as climate, diet, lifestyle and economic status. Factors related to the study design or sample size should also be put into consideration ( Brooks et al, 2012 and Li et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Younger Filipinos are more likely to consume diets that are high in fat, red meat, and dairy products compared with older Filipinos (Brooks, Leake, Parsons, & Pham, 2012). There may be heterogeneity in dietary responses to social and economic changes within strata of socioeconomic status (Kelles & Adair, 2009).…”
Section: Introductionmentioning
confidence: 99%